ILHAQ DALAM BAHTSUL MASA'IL NU; ANTARA IJTIHAD DAN IKHTIYAT - Ma'mun, Sukron (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
This study tries to analyze several results of law decisions of Bahtsul Masa'il NU (BMNU) decided by using ilhaq method. It is one of the methods in law establishment used by BMNU. The way it works is similar to qiyas; however, conducting qiyas used by BMNU does not refers directly to the Qur'an or hadits, but it refers to the 'ulama's views available in the classical Arab texts. It is an atypical method in ushul al-fiqh studies, but it is, as a matter of fact, used by NU 'ulama'. This method, by all means, causes many strictures and questions from some of the ushul 'ulama’. Therefore, this study is based on two basic questions as fallow: 1) how is the process of ilhaq method in BMNU?; 2) how is this method viewed based on ushul al-fiqh perspective?. The result of this study shows that ilhaq conducted by BMNU is methodologically crumbly, but the products of its laws are not contradiction with the Qur’an and hadits as well as maqashid asy-syar’iyyah (the oqjectives of law).